High temperature mechanical behavior of ceramic composites - Nair, Shantikumar Vasudevan, 1953-; Jakus, Karl (Butterworth-Heinemann, 1995)
Covers the mechanical behavior of ceramic matrix composites at elevated temperatures. Topics include both short-term behavior (strength, fracture toughness, and R-curve behavior) and long-term behavior (creep, creep-fatigue, delayed failure, and lifetime).
Keywords: Ceramic-matrix composites -- Mechanical properties.; Materials at high temperatures.; elektronické knihy; electronic books